Far-Red Light Accelerates Photosynthesis in the Low-Light Phases of Fluctuating Light. (16th October 2019) - Kono, Masaru; Kawaguchi, Hikaru; Mizusawa, Naoki; Yamori, Wataru; Suzuki, Yoshihiro; Terashima, Ichiro
Abstract: It is well known that far-red light (FR; >700 nm) drives PSI photochemistry, but its effect on photosynthetic performance has received little attention. In this study, the effects of the addition of FR to red fluctuating light (FL) have on photosynthesis were examined in the leaves of Arabidopsis thaliana . Light-activated leaves were illuminated with FL [alternating high light/low light (HL/LL) at 800/30 μmol m −2 s −1 ] for 10–15 min without or with FR at intensities that reflected natural conditions. The CO2 assimilation rates upon the transition from HL to LL were significantly greater with FR than without FR. The enhancement of photosynthesis by FR was small under the steady-state conditions and in the HL phases of FL. Proton conductivity through the thylakoid membrane (gH + ) in the LL phases of FL, estimated from the dark relaxation kinetics of the electrochromic absorbance shift, was greater with FR than without FR. The relaxation of non-photochemical quenching (NPQ) in the PSII antenna system and the increase in PSII photochemistry in the LL phases accelerated in the presence of FR. Similar FR-effects in FL were confirmed in typical sun and shade plants. On the basis of these results, we concluded that FR exerted beneficial effects on photosynthesis in FL by exciting PSI and accelerating NPQ relaxation and PSII-yield increase. This was probably because of the increased gH +, which would reflect faster ΔpH dissipation and ATP synthesis.